2019
DOI: 10.1038/s41598-019-52606-7
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour-stroma ratio and 5-year mortality in gastric adenocarcinoma: a systematic review and meta-analysis

Abstract: Tumour-stroma ratio (TSR) is a novel potential prognostic factor in cancers and based on the proportions of stroma and tumour area. The prognostic value of TSR in gastric cancer is incompletely known. The aim of this study was to estimate prognostic significance of TSR in gastric adenocarcinoma. A search of PubMed (MEDLINE), Web of Science, EMBASE, Cochrane and Scopus databases was performed. A meta-analysis was conducted on five-year survival in gastric cancer patients using inverse variance random-effects me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The majority of previous studies have indicated a negative prognostic impact of a dense tumour stroma, most often measured as the tumour stroma ratio (TSR), e.g. in colorectal cancer [16] , [17] , [18] , gastric cancer [19] , breast cancer [ 20 , 21 ], cervical cancer [22] , and oesophageal squamous cell cancer [23] . This association was also confirmed in a meta-analysis including 14 studies of different cancer types [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies have indicated a negative prognostic impact of a dense tumour stroma, most often measured as the tumour stroma ratio (TSR), e.g. in colorectal cancer [16] , [17] , [18] , gastric cancer [19] , breast cancer [ 20 , 21 ], cervical cancer [22] , and oesophageal squamous cell cancer [23] . This association was also confirmed in a meta-analysis including 14 studies of different cancer types [12] .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that intratumor stroma proportions have been proposed as significant indicators of GC prognosis (Lee et al, 2017). Previous studies have suggested that a high matrix proportion in GC patients means a poor prognosis (Ham, Lee & Hur, 2019;Kemi, Eskuri & Kauppila, 2019;Lee et al, 2017). Collagen genes play a crucial role in cell matrix formation, and their abnormal expression may lead to changes in matrix proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Additional data, including height, BMI, FAO p and ETS, were included when available. Externally sourced data were extracted using WebPlotDigitizer 109 (Web Plot Digitizer, v.4.2, 2019, Ankit Rohatgi, https://autom eris.io/WebPl otDig itizer, Pacifica, California, USA) [110][111][112][113] if not presented in table or text. Verification of data extraction accuracy was substantiated using a subset of our own publications 94,108,114,115 to compare extracted values to the actual measured values (n = 80).…”
Section: External Data Extractionmentioning
confidence: 99%